High-energy and long-life O3-type layered cathode material for sodium-ion batteries - Xinghui Liang; Xiaosheng Song; H. Hohyun Sun; Hun Kim; Myoung-Chan Kim; Yang-Kook Sun (Nature Communications)
Abstract O3-type layered oxide for sodium-ion batteries have attracted significant attention owing to their low cost and high energy density. However, their applications are restricted by rapid capacity decay during long-term cycling, with uneven Na+ distribution and microcrack formation being key contributing factors. In this study, a customized reconstruction layer integrating a fast ion conductor NaCaPO4 coating with gradient Ca2+ doping is developed to enhance the surface chemical and mechanical stability of the layered cathodes. The gradient Ca2+ doped interphase facilitates uniform phase transformation within the particles, minimizes lattice mismatch, ensures even Na+ distribution, and mitigates microcrack formation through a pinning effect. Consequently, the optimized sample exhibits improved electrochemical performance and robust reliability under high-voltage conditions and a broad temperature range (−10 to 50 °C). The practical feasibility of a pouch-type full cell paired with a hard carbon anode is demonstrated by a high capacity retention of 82.9% after 300 cycles at 0.5 C. This scalable interface modification strategy provides valuable insights into the development of advanced oxide cathode materials for sodium-ion batteries.